The Evidence on School-Based Health Centers: A Review. (February 2019) - Arenson, Michael; Hudson, Philip J.; Lee, NaeHyung; Lai, Betty
Context . Pediatricians working toward health equity require health care delivery mechanisms that take on dual roles: mitigating the health effects of a maladaptive social ecosystem while simultaneously working to improve the ecosystem itself. School-based health centers (SBHCs) perform these dual roles by providing medical, mental/behavioral, dental, and vision care directly in schools where young people spend the majority of their time, maximizing their opportunity to learn and grow. Evidence Acquisition . Databases were searched extensively for research studies published between January 2000 and December 2018. Evidence Synthesis . The authors began with 3 recent high-impact reviews that covered SBHC history, health outcomes, cost-benefit, and impact on health equity. Informed by these articles, the authors organized the evidence into 4 broad categories of impact: Financial, Physical Health (including medical, vision, and dental), Mental Health, and Educational Outcomes. Using these 4 categories, the authors then performed a robust literature search using PubMed for studies that fit into these themes. Conclusions . SBHCs increase access to health services for children, families, and communities, which ultimately leads to positive short- and long-term outcomes in service of a broad range of stakeholders. Educational impact requires further attention on both outcomes and methodological approaches. Three current public health topics of importance were identified that SBHCs might be well-suited to address: Youth Gun Violence, Adverse Childhood Experiences, and the Health of American Indian/Alaskan Native communities in the United States.